Komunikasi Persuasif Melalui Pesan Akun Instagram Badan Narkotika Nasional Provinsi Papua - Izaac, Fransina Alfonsina; Pamangin, Lisda Oktavia Madu; Violita, Fajrin; Mantayborbir, Vyona; Tuturop, Katarina Lodia (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study provides an overview that social media, especially Instagram, has great potential as a means of persuasive communication in drug prevention campaigns. The strategy for preventing drug abuse is carried out by the Papua Province National Narcotics Agency through the Instagram platform. Messages about the dangers and impacts of drugs are conveyed through images and videos uploaded to Instagram accounts. This study looks at the input aspects in the theory of persuasive communication, namely the content of the message, the purpose of the message, and the characteristics of the message in the Instagram posts of the Papua Province National Narcotics Agency. The posts analyzed were image posts containing drug prevention messages. The image posts selected from January to March 2025 totaled 18 images. This research method uses a descriptive qualitative research method. The results of the study found that the composition of the message content of the post consisted of three, namely, fear appeal, emotional appeal and motivational appeal. The purpose of the message conveyed is education, providing information and influencing. The targets depicted in the Instagram posts of the Papua Province National Narcotics Agency are teenagers, considering that teenagers are the age group that is most involved in drug abuse according to data from the Papua Province National Narcotics Agency.